Method for covalently binding biomolecules to plastics
By using a mixture of carbon-containing gas to perform plasma enhanced chemical vapor deposition under pulse bias and depositing plasma activated coating, the problem of covalent fixation of biomolecules on microporous plates is solved, and a rapid, reproducible and long-term reactive biomolecule fixation effect is achieved.
Patent Information
- Application Number
- CN202380058794.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-09
- Filing Date
- 2023-08-09
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art is difficult to quickly and reproducibly covalently immobilize biomolecules on microplates, especially in the nonuniform reactivity on plastic surfaces.
Plasma-enhanced chemical vapor deposition (PECVD) method under pulse bias is used to deposit plasma activated coatings (PAC) on plastic surfaces using a mixture of carbon-containing gases to achieve covalent fixation of biomolecules.
This method achieves rapid and reproducible covalent fixation of biomolecules, improves the reactive coverage of plastic surfaces, is suitable for the pores of microporous plates, and maintains reactivity for a long time.
Smart Images

Figure CN119677801A_ABST
Abstract
Description
[0001] This application claims priority to Australian Provisional Patent Application No. 2022902232 (filed on August 9, 2022), the contents of which are incorporated herein in their entirety. Technical Field
[0002] The present invention relates to methods for covalently bonding biomolecules to plastics. In particular, the present invention relates to plasma activated coatings of plastic wells or dishes to which biomolecules are covalently bonded. However, it should be understood that the present invention is not limited to this particular field of use. Background Art
[0003] Any discussion of the prior art throughout the specification should not be considered as an admission that such prior art is widely known or forms part of the common general knowledge in the field.
[0004] By immobilizing biomolecules or cells on a solid support, microplates provide a fast and convenient platform to study biological processes in high-throughput assays. Common applications include enzyme-linked immunosorbent assays (ELISA) and biomolecular interaction studies. The standardized microplate format facilitates robust characterization by performing fluorescence and colorimetric detection in an automated optical microplate reader with a small sample volume. Commercially available microplates are typically made of plastics (e.g., polystyrene) that are modified by tissue culture surface treatments that reduce hydrophobicity and enhance cell adhesion. However, due to the inert nature of polystyrene, additional surface functionalization is required to immobilize biomolecules for solid phase assays. Biomolecules of interest include proteins, such as antibodies and streptavidin, as well as smaller molecules, such as DNA and peptides. For example, DNA probes are immobilized on microplates for accurate DNA detection and as a scaffold for DNA-guided assembly of multi-enzyme complexes. However, current biomolecule immobilization methods have limitations, such as physical adsorption and chemical activation.
[0005] Most commonly, physical adsorption is used to attach biomolecules (e.g., DNA and streptavidin) to microplate surfaces via hydrophobic or electrostatic interactions. However, physically adsorbed biomolecules bind weakly to microplates in random orientations and are sensitive to changes in ion concentration, pH, and heat, resulting in reduced reproducibility. Proteins can also be denatured by physical adsorption, for example reducing monoclonal antibody activity to less than 10%.
[0006] Stronger and more specific binding can be achieved by chemical activation of the microplate wells, which increases stability, activity, and wash resistance, and reduces competitive protein exchange. Silane chemistry, such as aminopropyltriethoxysilane (APTES), is commonly used to activate surfaces for biomolecule binding. This surface activation approach has been used for DNA microarrays, where the DNA is functionalized with thiol or amine groups prior to chemical coupling to the surface. However, chemical activation methods are multi-step processes, often require modified biomolecules, such as amine-modified or thiol-modified DNA oligonucleotides, and may involve cytotoxic agents that must be completely removed prior to downstream applications in cell culture.
[0007] Plasma immersion ion implantation (PIII) has been used previously to immobilize biomolecules on plastics (Bilek & McKenzie, Biophysical Reviews 2010, 2, 55-65; Nosworthy et al., Acta Biomaterialia 2007, 3, 695-704; Kosobrodova et al., ACS Applied Materials & Interfaces 2018, 10, 227-237). In PIII, high-energy ions from a non-carbon-containing gas (e.g., nitrogen, argon, or helium) bombard the polymer surface to create a reservoir of free radicals beneath the surface of the polymer to which the biomolecules can covalently bind. Although this method is rapid, reproducible, and the reactivity of these surfaces remains for a long time, the reactivity of the plastic surface is not uniform due to the shielding effect caused by the pore walls, making this method unsuitable for treating the wells of microplates.
[0008] Alternative plasma-based methods, such as argon plasma activation and nitrogen plasma activation, have previously been used for microplates (North et al., ACS Applied Materials & Interfaces 2010, 2, 2884-2891; Boulares-Pender et al., Journal of Applied Polymer Science 2009, 112, 2701-2709). However, these methods require chemical activation steps and specific functional groups on biomolecules. In addition, the density of active groups introduced by these methods is limited by the type of gas mixture required to produce a mechanically strong surface coating. Another method involves direct deposition of atomized proteins, such as collagen, on microplates by dielectric barrier discharge plasma (O'Sullivan et al., ACS Omega 2020, 5, 25069-25076). However, this method requires a large amount of protein and not all biomolecules incorporated into the coating are accessible on the surface.
[0009] Therefore, there is a need for rapid and reproducible methods to covalently bind biomolecules to microplate wells for extended periods of time.
[0010] It is an object of the present invention to overcome or ameliorate at least one of the disadvantages of the prior art, or to provide a useful alternative. Summary of the invention
[0011] It has surprisingly been found that plasma enhanced chemical vapor deposition (PECVD) using a mixture of carbon-containing gases under pulsed bias produces plasma activated coatings (PACs) on plastic surfaces that enable covalent fixation of biomolecules. The method is rapid and reproducible, and the reactivity of the plastic surface can be maintained for a long time. In addition, the coverage of the reactivity of this method is significantly improved compared to other plasma activation methods (e.g., PIII), making it suitable for wells of culture dishes and microplates.
[0012] In one aspect, the present invention provides a method for coating a plastic surface, the method comprising:
[0013] (a) treating the plastic surface with ions under a pulsed bias; and
[0014] (b) depositing plasma on the plastic surface by plasma enhanced chemical vapor deposition (PECVD) of a gas mixture comprising acetylene and argon under a pulsed bias,
[0015] wherein a mesh is placed over the plastic surface such that the plasma passes through the mesh before being deposited on the plastic surface, and wherein the method produces a plasma activated coating (PAC) covalently bound to biomolecules on the plastic surface.
[0016] In one embodiment, the ions are from an inert gas.
[0017] In one embodiment, the ions are argon ions.
[0018] In one embodiment, the gas mixture further comprises nitrogen.
[0019] In one embodiment, the atmospheric percentage of nitrogen in the gas mixture is 35% or less.
[0020] In one embodiment, the atmospheric percentage of nitrogen in the gas mixture is about 21%.
[0021] In one embodiment, the treatment with ions is performed at an RF power of about 5 to about 300 W and a negative pulse bias of about 1 to about 1000 V for about 0.5 to about 30 minutes.
[0022] In one embodiment, the treatment with ions is performed at an RF power of about 50 to about 100 W and a negative pulse bias voltage of about 300 to about 700 V for about 1 to about 15 minutes.
[0023] In one embodiment, the treatment with ions is performed at an RF power of about 75 W and a negative pulse bias of about 500 V for about 2 minutes.
[0024] In one embodiment, plasma deposition is performed at a plasma discharge of about 5 to about 300 W and a negative pulse bias of about 1 to about 1000 V for about 10 to about 30 minutes.
[0025] In one embodiment, plasma deposition is performed at a plasma discharge of about 10 to about 100 W and a negative pulse bias of about 300 to about 700 V for about 10 to about 30 minutes.
[0026] In one embodiment, plasma deposition is performed at a plasma discharge of about 50 W and a negative pulse bias of about 500 V for about 10 to about 30 minutes.
[0027] In one embodiment, the gas mixture is maintained at about 110 mTorr.
[0028] In one embodiment, the negative pulse bias is applied at a frequency of about 0.5 to about 10 kHz and a pulse duration of about 1 to about 100 μs.
[0029] In one embodiment, the negative pulse bias is applied at a frequency of about 1 to about 5 kHz and a pulse duration of about 5 to about 30 μs.
[0030] In one embodiment, the negative pulse bias is applied at a frequency of about 3 kHz and a pulse duration of about 20 μs.
[0031] In one embodiment, the mesh is formed from a conductive metal.
[0032] In one embodiment, the mesh forms the lid of a Faraday cage surrounding the plastic surface.
[0033] In one embodiment, the mesh has 50 openings per linear inch.
[0034] In one embodiment, the conductive metal is stainless steel.
[0035] In one embodiment, the plastic surface has a non-planar geometry.
[0036] In one embodiment, the plastic surface is a microplate well or a culture dish.
[0037] In one embodiment, the plastic is polystyrene.
[0038] In one embodiment, the biomolecule is a nucleic acid.
[0039] In one embodiment, the biomolecule is a protein.
[0040] In one embodiment, the protein is streptavidin or laminin.
[0041] In one embodiment, the PAC has a surface nitrogen concentration of about 4% to about 14%.
[0042] In one embodiment, the PAC has a relative radical density of about 0.016 to about 0.021.
[0043] In one embodiment, the PAC has an average absorption of about 0.052 to about 0.056 au at 450 nm.
[0044] In one embodiment, the PAC has a thickness of about 20 nm.
[0045] In one embodiment, PAC is present at about 2×10 11 About 5x10 11 Molecules / cm 2 Hybridize DNA at a concentration of .
[0046] In one embodiment, PAC is present at about 2×10 11 About 9x10 11 Molecules / cm 2 The concentration of streptavidin was fixed.
[0047] In one embodiment, a Faraday cage with a mesh cover includes an open container, a mesh cover, and a cap for securing the mesh cover to the open container, wherein the container, the mesh cover, and the cap are all formed of a conductive metal.
[0048] In another aspect, the present invention provides a plastic surface coated with a plasma activated coating (PAC) when produced by the method of the present invention.
[0049] In another aspect, the present invention provides a plastic surface coated with a plasma activated coating (PAC), wherein the PAC has a surface nitrogen concentration of about 4% to about 14%.
[0050] In another aspect, the present invention provides a plastic surface coated with a plasma activated coating (PAC), wherein the PAC has a free radical relative density of about 0.016 to about 0.021.
[0051] In another aspect, the present invention provides a plastic surface coated with a plasma activated coating (PAC), wherein the PAC has an average absorption of about 0.052 to about 0.056 au at 450 nm.
[0052] In another aspect, the present invention provides a plastic surface coated with a plasma activated coating (PAC), wherein the PAC has a thickness of about 1 nm to about 10 nm.
[0053] In another aspect, the present invention provides a plastic surface coated with a plasma activated coating (PAC), wherein the PAC has a thickness of about 2 nm.
[0054] In another aspect, the present invention provides a plastic surface coated with a plasma activated coating (PAC), wherein the PAC is at about 2×10 11 About 5x10 11 Molecules / cm 2 The concentration of hybridized DNA.
[0055] In another aspect, the present invention provides a plastic surface coated with a plasma activated coating (PAC), wherein the PAC is at about 2×10 11 About 9x10 11 Molecules / cm 2 The concentration of streptavidin was fixed.
[0056] In another aspect, the present invention provides a plastic surface coated with a plasma activated coating (PAC), wherein the PAC is bound to laminin. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 : (a) Percentage of surface element concentrations of PS microplates treated with UT, TC, PIII, and PAC. (b) Relative electron paramagnetic resonance (EPR) integrated intensity between UT PS, PIII, and PAC-treated PS. The measured EPR signals were integrated and normalized by the radical penetration depth (PIII) or deposition (PAC). (c) Effective depth of PIII treatment of polystyrene and PAC thickness obtained from ellipsometry measurement of PAC-treated silicon wafers. (d) Water contact angle of UT, TC, PIII, and PAC-treated PS sheets placed in 96-well microplates during plasma treatment. (e) Dispersive and polar components of the surface free energy of UT, TC, PIII, and PAC-treated PS microplates, calculated by the Owens-Wendt-Rabel-Kaelble method. Error bars represent their standard errors. (f) Average absorbance and autofluorescence with SD for PS microplates treated with UT (circles), PIII (squares), and PAC (triangles). SD bars are hidden when they are smaller than the marker size. The left column and y-axis show the absorbance at 450 nm, and the right column and y-axis show the autofluorescence emission intensity at five excitation / emission wavelengths.
[0058] Figure 2 : (a) Schematic diagram showing the oligonucleotide immobilization method and an example of data plotted on one graph. Fluorescence intensity was measured at steps 1, 3, 5, 7, 8, 9 and 11 and is shown on the graph. (b) Distribution of DNA hybridized on a PAC-treated microplate by a microplate reader. (c) Alexa647 fluorescence intensity of DNA immobilized (pH 4) and hybridized on TC, PIII and PAC-treated microplates with baseline subtracted.
[0059] Figure 3 : (a) Immobilization and hybridization of DNA on PIII treated microplates at pH 3-8. (b) Immobilization and hybridization of DNA on PAC treated microplates at pH 3-8. (c) Immobilization and hybridization of DNA to PIII treated microplates (1 week, 1 month and 3 months after treatment). (d) Immobilization and hybridization of DNA to PAC treated microplates (1 week, 1 month and 3 months after treatment).
[0060] Figure 4 : DNA fixed density on microplates treated with PIII and PAC. Cy3-labeled DNA (20x A-GCTCTGCAATCAACTTATCCC-C y3) was fixed on microplates treated with plasma, and Cy3 intensity was measured after a washing step. The trend of fixed DNA density was similar to that of hybridized DNA density. This suggests that the lower hybridization density on some samples is not caused by overcrowding of fixed DNA on the surface.
[0061] Figure 5 : Streptavidin immobilized on microplates. (a) Cy3 fluorescence intensity of streptavidin-Cy3 immobilized on TC, PIII, and PAC treated microplates. (b) The ability of immobilized streptavidin to bind to biotin. (c) Immobilization of streptavidin on PIII treated microplates at pH 3-9. (d) Immobilization of streptavidin on PAC treated microplates at pH 3-9. (e) Streptavidin immobilized on 1 week, 1 month, and 3 month old PIII treated microplates. (f) Streptavidin immobilized on 1 week, 1 month, and 3 month old PAC treated microplates.
[0062] Figure 6 : Three different conditions, each with a 3-mesh size, for plasma treatment to reduce nanoparticle deposition in cell culture plate wells
[0063] Figure 7 : Faraday cage plate holder from top view (A), bottom view (B) and sketch with dimensions (C).
[0064] Figure 8: A diagram showing a plasma processing chamber containing a plate to be treated with plasma.
[0065] Fig. 9 : Nanoparticle counting using flow cytometry.
[0066] Fig.10 : SEM images taken on silicon wafers located inside a 24-well plate, plasma treated without a mesh (A, B) and under a Faraday cage with a 50 mesh cover (C, D). Images were taken at 1000x magnification (A, C) and 5000x magnification (B, D).
[0067] Fig.11 : Thickness of PAC measured by plasma deposition on silicon wafers located in various holes and using different processing conditions.
[0068] Fig.12 : Comparison of PAC thickness deposited on a 24-well plate without mesh and a Faraday cage with a 50 mesh lid. Shading is used to illustrate different thickness ranges.
[0069] Fig.13 : Comparison of all three plates showing the percentage of surface area coverage of jumping colonies observed in each well. 24-well plates without plasma treatment (Untreated), plasma treatment without mesh (-Mesh), and plasma treatment with a Faraday cage with a 50 mesh cover (+Mesh). All plates were incubated with Laminin 521 before cell seeding. Cells were cultured for up to 41 days. DETAILED DESCRIPTION
[0070] definition
[0071] In describing and claiming the present invention, the following terms are used in accordance with the definitions listed below. It should also be understood that the terms used herein are only for the purpose of describing specific embodiments of the present invention and are not intended to be limiting. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs.
[0072] As used herein, the term "about" may mean within 1 or more standard deviations according to the practice in the art. Alternatively, "about" may mean a range of up to 20%. When specific values are provided in the specification and claims, it should be assumed that the meaning of "about" is within an acceptable error range for that specific value.
[0073] In the context of the present invention, the term "subject" includes any human or non-human animal. The term "non-human animal" includes all vertebrates, such as mammals and non-mammals, such as non-human primates, horses, cows, dogs, etc.
[0074] In the context of the present invention, the words “comprise”, “comprising” and the like should be interpreted in an inclusive rather than exclusive sense, ie, in the sense of “including but not limited to”.
[0075] The terms "preferred" and "preferably" refer to embodiments of the present invention that may provide certain benefits in certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. In addition, the recitation of one or more preferred embodiments does not mean that other embodiments are not useful, and is not intended to exclude other embodiments from the scope of the present invention.
[0076] Other than in the operating examples, or where otherwise indicated, all numbers expressing quantities of ingredients or reaction conditions used herein are to be understood as modified in all instances by the term "about".
[0077] The description of numerical ranges using endpoints includes all numbers subsumed within that range (eg, 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, 5, etc.).
[0078] The term "au" means absorbance units.
[0079] The term "biomolecule" refers to molecules found in living organisms, such as amino acids, lipids, carbohydrates, proteins, polysaccharides, and nucleic acids.
[0080] The terms "culture plate", "microplate", "microtiter plate", "microwell plate", "multiwell plate" and ELISA plate refer to a plate containing, for example, 6, 12, 24, 48, 96, 384 or 1536 sample wells arranged in a 2:3 rectangular matrix. Individual wells can hold liquids from nanoliters to milliliters and can be round or square.
[0081] The terms "Petri dish" and "culture dish" refer to a shallow cylindrical dish that can be used to contain growth medium in which cells can be cultured.
[0082] The term "non-planar geometry" refers to a structure that is not completely inclined or constrained to a single plane. Such a structure is not substantially flat in shape and has more than 2 dimensions (e.g., walls and a base). Non-planar geometries include U-shaped, V-shaped, and flat-bottomed wells, ELISA plates, culture dishes, and petri dishes.
[0083] As used herein, the term "pulse duration" refers to the time during which the pulse bias is applied in each pulse.
[0084] As used herein, the term "Faraday cage" refers to a container formed from an electrically conductive material.
[0085] Preferred embodiments of the present invention
[0086] Although the invention has been described with reference to certain embodiments detailed herein, other embodiments can achieve the same or similar results. Variations and modifications of the invention will be apparent to those skilled in the art, and the invention is intended to cover all such modifications and equivalents.
[0087] The invention is further described by the following non-limiting examples.
[0088] Example
[0089] Example 1 - Microplate Preparation
[0090] In this study, high-energy plasma treatment was performed on TC-treated polystyrene (PS) microplates (CLS3603) (Sigma-Aldrich) and compared with unmodified TC-treated PS microplates and untreated (UT) PS microplates (CLS3370). All microplates were made of polystyrene (PS). These microplates had wells of approximately 6 mm in diameter and approximately 11 mm in depth. When the microplates were placed on a PIII or PAC stainless steel holder, there was a 2-3 mm gap between the holder and the bottom of the wells. Molded aluminum foil was used to fill the gap in order to improve contact with the holder. Prior to plasma treatment, the microplates were cut into quarters with a hot wire cutter so they could be mounted on the sample holder in our small prototype plasma reactor and taped together on the back for DNA and streptavidin immobilization and fluorescence detection.
[0091] Example 2 - PIII Treatment
[0092] The PIII process was performed using an inductively coupled radio frequency (RF) power (ENI RF power generator) at 13.56 MHz to generate the plasma, and a negative bias was applied to the stainless steel sample holder to accelerate the positive ions toward the sample. The pressure inside the chamber was evacuated to 5×10 -5 Torr or less, and high purity nitrogen is introduced during treatment and maintained at 2 mTorr. When matched, the RF forward power is 100W and the reverse power is 12W. The microplate with or without aluminum foil is attached to a stainless steel holder, where the stainless steel mesh is placed 5 cm from the holder and conductively connected to it. Nitrogen ions are accelerated toward the stainless steel holder through the mesh at a frequency of 50 Hz with a 20 kV negative bias pulse of a duration of 20 μs. The microplate is treated for 400 or 800 seconds (PIII400 or PIII800).
[0093] Example 3 - PAC Treatment
[0094] PAC treatment was performed in a separate plasma system using capacitively coupled RF power at 13.56 MHz (Eni OEM-6) and a negative pulsed bias generated by a RUP6 pulse generator (GBS Elektronik GmbH, Dresden, Germany). The microplate was placed on a stainless steel sample holder connected to the RUP6, with aluminum foil placed under the microplate to eliminate the air gap between the sample holder and the plate and to enhance the accelerating electric field at the plate surface. The chamber was evacuated to 5 × 10 -5 Torr or less. Before plasma coating, the microplate was activated with argon ions for 2 minutes at an RF power of 75W and an applied bias of 500V to promote coating adhesion. The argon pressure inside the chamber was maintained at about 70-80 mTorr. For PAC deposition, a reactive gas mixture of acetylene, nitrogen and argon was introduced into the chamber. The ratio between the gases was controlled by a mass flow controller (Allicat Scientific), and the pressure in the chamber was maintained at 110 mTorr during coating deposition. Plasma deposition was performed for 10 or 30 minutes with a plasma discharge of 50W and a negative bias voltage of 500V. A negative bias from RUP6 was applied at a frequency of 3kHz and a pulse duration of 20μs. Four different gas ratios were selected for comparison: no nitrogen (0% nitrogen), low nitrogen (21% nitrogen), medium nitrogen (71% nitrogen) and high nitrogen (93% nitrogen) (Table 1). A separate PAC treatment was performed on a smooth silicon wafer with a native oxide layer to measure coating thickness.
[0095] Table 1: PAC treatment using four different gas flow rate recipes
[0096]
[0097] Upon exposure to air, free radicals on the treated surface reacted with oxygen in the air to form oxygen-containing groups. These changes to the surface chemistry saturated after one week, so after each treatment, the microplates were covered in aluminum foil and stored in air at room temperature for at least one week prior to all subsequent analysis and biomolecule immobilization.
[0098] Example 4 - Chemical composition of PAC and PIII modified microplates
[0099] The coating thickness of PAC was calculated using ellipsometry. Silicon wafer was used as substrate to measure the coating thickness, and the coating was deposited with the various PAC formulations shown in Table 1. Ellipsometry data were collected at three incident angles (65 °, 70 ° and 75 °) using a JA Woollam M2000V spectroscopic ellipsometer. The model representing the PAC layer consisting of a silicon substrate, a silicon oxide layer (2 nm) and a Cauchy layer was used to fit the data to obtain film thickness.
[0100] The surface free energy of 96-well microplates treated with PIII and PAC treated TC (1 week after treatment) was calculated and compared with untreated polystyrene. The contact angles with two liquid probes (water and diiodomethane) were measured using a Theta tensiometer (Biolin Scientific). The results for each sample were averaged from 10 drops. The surface free energy was calculated using the Owens-Wendt-Rabel-Kaelble method.
[0101] To measure the radical density of the microplate after PIII and PAC treatment, a polystyrene film (Goodfellow, thickness 0.19 mm) was cut into 40 mm × 5 mm strips and treated with PIII or PAC. Polystyrene film was used as a substitute for microplates, which are not suitable for measuring instruments. Microwave absorption of unpaired electrons from samples was measured using an electron paramagnetic resonance (EPR) spectrometer (Bruker EMX X-band). Measurements were performed at room temperature with a microwave power of 2 mW and a frequency of 9.8 MHz. The magnetic field was scanned with a center value of 3523 G and a scan width of 200 G. Ten scans were measured for each sample. Similar measurements were applied to an EPR tube containing 2,2-diphenyl-1-picrylhydrazyl (DPPH) powder with a known radical density to calculate the number of unpaired electrons on each sample.
[0102] Changes in the surface chemistry of the microplates after PIII and PAC treatment were determined by comparing the FTIR-ATR spectra of untreated and treated polystyrene. The polystyrene membranes were cut into small discs and placed at the bottom of the wells of the microplates for PIII and PAC treatment. One week after treatment, the discs were analyzed using a Hyperion FTIR spectrometer (Bruker) equipped with a micro-germanium crystal ATR accessory. Each analysis was performed with a resolution of 4 cm -1 The 1490 cm -1 The intensities of the peaks were normalized to the spectra for comparison.
[0103] The chemical composition of the PIII-treated microplates was determined by XPS, comparing the treatment times of 400 s (PIII-400) and 800 s (PIII-800) ( Figure 1a). The oxygen content of the PIII-treated microplates (6.1-11.1%) was not significantly different from that of the TC-treated microplates (8.3%). Similarly, the surface nitrogen content was very low before (0.6%) and after (0.5-0.8%) PIII treatment. This is surprising because previous studies have shown that the nitrogen content increased (7-12%) after 400s PIII treatment of glass coverslips spin-coated with polystyrene (Kosobrodova et al., ACS Applied Materials & Interfaces 2018, 10, 227-237), and after polystyrene film treatment, the oxygen composition increased due to exposure to air (Kosobrodova et al., Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms 2013, 304, 57-66.41). The differences in the results observed here may be due to differences in the shape of the deep wells or in the type of polystyrene structure of the microplates compared to polystyrene membranes or spin-coated layers, such as the orientation of the phenol groups.
[0104] Long-lived free radicals arising in the modified surface layer have been proposed as the main mechanism for the covalent fixation of biomolecules on the PIII surface (Bilek et al., Proceedings of the National Academy of Sciences of the United States of America 2011, 108, 14405-14410). The radical density of free radicals in a sample can be calculated from the EPR intensity by comparison with the radical density obtained from a standard DPPH sample with a known radical density. However, due to differences in geometry and volume (DPPH powder was placed in an EPR tube, while PIII and PAC-treated PS strips were mounted on an EPR tube), we could not calculate the exact radical density on our samples. Instead, we assumed the same measurement area for all samples and compared the relative radical density in those samples by normalizing to the depth of plasma treatment.
[0105] For the PIII sample, a processing depth of 75 nm was assumed from the literature (Gan et al., Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms 2006, 247, 254-260.39). -6 , Figure 1 b) Compared to 400 and 800 s PIII (0.10 ± 0.001 and 0.24 ± 0.0003, respectively), the relative density of free radicals on the treated microplates was found to be significantly increased (one-way ANOVA, p < 0.0001). The increase from PIII-400 to PIII-800 was also significant (one-way ANOVA, p < 0.0001).
[0106] The wettability of the surface is another property known to be affected by PIII treatment. Here, the wettability of the surface was significantly higher than that of the TC-treated microplate (79.1 ± 0.6°)( Figure 1 d), it was observed that PIII treatment significantly (one-way ANOVA, p < 0.0001) reduced the water contact angle of the microplates treated with PIII-400 (45.5 ± 1.7°) and PIII-800 (37.0 ± 1.9°). The Owens-Wendt-Rabel-Kaelble method considers that the surface energy consists of polar and dispersed components. It was found that the polar component of the microplates treated with PIII (23.7 ± 0.3-30.1 ± 0.3 mJ / m 2 ) was significantly higher than that of the TC-treated microplate (4.8±0.1 mJ / m 2 , one-way ANOVA, <0.0001) and increased with treatment time ( Figure 1 e). The wettability and polar surface energy composition values of the PIII treated microplates have a stronger correlation with the relative radical density as described above than with the surface nitrogen and oxygen composition.
[0107] The chemical composition of the PAC microplates was determined by XPS, comparing four different gas formulations containing increasing amounts of nitrogen; no nitrogen, low nitrogen, medium (mod) nitrogen, and high nitrogen ( Figure 1a). Surface nitrogen was found to increase with nitrogen percentage (%) in all PAC formulations. The values measured ranged from TC (0.6%) to no nitrogen (4.0%), low nitrogen (9.7%), medium nitrogen (13.8%), and high nitrogen PAC (14.6%). For surface oxygen, the no nitrogen PAC treated microplates had increased surface oxygen (14.9%). The oxygen content of all other formulations (8.5-9.4%) was similar to that of the TC treated microplates (8.3%). It is important to note that the sampling depth measured by XPS (approximately 10 nm) can include the polystyrene substrate below the deposited layer, which would reduce the nitrogen percentage.
[0108] There was no significant difference in the relative density of free radicals between samples treated with different PACs ( Figure 1 b, no nitrogen 0.020 ± 0.01, low nitrogen 0.019 ± 0.0008, medium nitrogen 0.016 ± 0.013, high nitrogen 0.021 ± 0.0035). As mentioned above, these values are normalized by the PAC coating thickness ( Figure 1 c).
[0109] The water contact angle of the microplate decreased after PAC treatment ( Figure 1 d). There was no significant difference in water contact angle between low nitrogen PAC and medium nitrogen PAC, but high nitrogen was significantly more hydrophilic than no nitrogen (one-way ANOVA, p<0.0001). The water contact angle ranged between 42.1° and 65.1°. The polar component of the PAC samples also increased with increasing nitrogen content in the PAC formulation.
[0110] In general, it was found that the PIII microplates had a low surface nitrogen composition, a high relative radical density, and were very hydrophilic. The PAC microplates had a high nitrogen composition, a moderate relative radical density, and were more hydrophilic than the untreated plates. It was found that the PIII and PAC treated microplates differed in many measured parameters. Compared with the PIII treated microplates, the PAC treated microplates had significantly higher surface nitrogen amounts (PIII 0.5-0.8%, PAC 4-14.6%), while the PIII treated microplates had a higher relative radical density (PIII 0.10-0.24, PAC 0.016-0.021), and were more hydrophilic (37.0°-45.5°) than all PACs (50.7°-65.1°) except the high nitrogen treatment (42.1°). The relative radical density appears to have a greater correlation with surface hydrophilicity than the surface nitrogen and oxygen composition.
[0111] Example 5 - Optical properties of PIII and PAC modified microplates
[0112] Changes in optical properties can affect the utility of plasma-activated microplates, as optical readout is the primary detection method for biochemical plate assays. Changes in absorbance and autofluorescence after PIII and PAC treatment of microplates were measured with a PHERAstar FSX (BMG Labtech) and compared to untreated microplates. Absorbance was measured at 450 nm with 22 flashes per well using top optics. Fluorescence intensity was measured at five commonly used excitation and emission wavelengths using five optical modules (460 / 510, 485 / 520, 540 / 580, 575 / 620, 635-20 / 680-20). For each endpoint measurement, the center of the well was scanned with 10 flashes using top optics, the focus height was adjusted for each sample, and the gain was set to 1400.
[0113] Characterization of the effects of PIII and PAC treatment on absorbance and autofluorescence ( Figure 1 f). The absorbance was measured at 450 nm because this wavelength is used in many assays, such as HRP colorimetric assays. It was found that the average absorbance at 450 nm for PIII (0.150-0.207 au) and PAC (0.052-0.056 au) was significantly higher than that for untreated microplates (0.046 ± 0.001 au) (one-way ANOVA, p < 0.0001). The maximum increase in absorbance was observed for PIII-800 (0.207 ± 0.008 au), followed by PIII-400 (0.150 ± 0.010 au). Browning of the transparent microplates treated with PIII was also visible to the naked eye and increased with the treatment time. This browning may be due to the aggregation of carbonized structures in the modified layer, the number and size of which increase with longer treatment time. Compared with non-aluminum samples (0.030 au), the PIII samples with aluminum have smaller absorbance changes over multiple wells (0.016 au), indicating that aluminum modification improves the uniformity of treatment across the microplate. Compared with the microplates treated with PIII (3.36-4.5 times), the microplates treated with PAC have much smaller absorbance increases (1.13-1.22 times), while there are no significant differences between PAC gas treatments (0.052-0.056 au, one-way ANOVA, p>0.1). Overall, PIII causes a large increase in absorbance at 450 nm relative to untreated microplates (288%), while PAC has a more moderate (17.5%) relative increase.
[0114] Typically, aromatic polymers have high autofluorescence at shorter wavelengths due to low energy π to π* transitions. This is consistent with the observations here, where all untreated and treated microplates have higher autofluorescence at shorter wavelengths (460 / 510 and 485 / 520nm) than at longer wavelengths (540 / 580, 575 / 620, 635 / 680nm). In addition to this trend, PAC-treated microplates also had significantly higher autofluorescence at shorter wavelengths (162-196, one-way ANOVA, p<0.0001) compared to untreated (155-157), while PIII-treated microplates had significantly lower autofluorescence (100-144, one-way ANOVA, p<0.0001). In the PIII treatment, the aromatic rings are partially amorphized, which explains the lower autofluorescence observed for PIII and is supported by the observation that PIII-800 (100-118) has lower autofluorescence than PIII-400 (126-144). In contrast, at longer wavelengths, the differences in autofluorescence for all samples are smaller. Overall PAC and PIII treatments change microplate autofluorescence at shorter wavelengths (510-520nm), but they have smaller changes at longer wavelengths (580-680nm). The changes at shorter wavelengths are smaller relative to the total autofluorescence from the polystyrene substrate, with PAC giving an 8% increase and PIII giving a 27% decrease. At longer wavelengths, PAC increased by 9% and PIII decreased by 14% compared to untreated polystyrene.
[0115] Example 6 - DNA oligonucleotide immobilization in PIII and PAC modified microplates
[0116] For application in DNA binding assays, it is important for the immobilized DNA to maintain its ability to hybridize to complementary DNA oligonucleotides.Thus, the test focuses on the density of hybridized DNA as detected by the Alexa-647 fluorophore covalently attached to the hybridizing DNA oligonucleotide.
[0117] A 21 nucleotide (nt) ssDNA sequence (IDT DNA) was designed with a linker of 20 additional adenine nucleotides (Table 3). It was expected that under acidic conditions, the amine groups in the adenine nucleotides of the linker would be protonated, and thus the linker would be preferentially electrostatically attracted to the negatively charged plasmon surface compared to the core DNA sequence.
[0118] The wells of untreated, PIII and PAC treated 96-well microplates were incubated with 40 μL of 2 μM ssDNA in 10 mM citric acid / sodium citrate buffer at pH 3, 4, 5 or 6 or disodium hydrogen phosphate / sodium dihydrogen phosphate buffer at pH 7 or 8 for 1 hour at room temperature on a shaker. The DNA solution was replaced with 200 μL of 1% BSA (in 10 mM PBS, pH 7.4) for 1 hour at room temperature on a shaker to block the remaining active surface. The BSA solution was removed and the wells were washed three times with 200 μL of 2% SDS under vigorous shaking. After rinsing three times with 200 μL of MilliQ water, DNA hybridization was performed by adding a 21-nt complementary DNA strand (IDT DNA) modified with a 3'Alexa647 fluorophore. Complementary DNA was added to hybridization buffer (composed of 2mM magnesium chloride (Sigma-Aldrich), 1x Tris EDTA (Sigma-Aldrich), 1% BSA and 0.6% SDS) to a final concentration of 0.8 μM. Each well was incubated on a shaker at room temperature for 1 hour with 40 μL of 0.8 μM complementary DNA solution. After removing the solution, the wells were washed three times with 200 μL 10 mM PBS under vigorous shaking. Then, the wells were washed three times with 200 μL of 3 kinds of washing buffers under vigorous shaking; washing buffer 1 (2x saline-sodium citrate (SSC) + 0.6% SDS), washing buffer 2 (0.2xSSC + 0.6% SDS) and washing buffer 3 (0.1xSSC + 0.5% Tween 20). After rinsing the wells with 200 μL of 10 mM PBS, each well was filled with 40 μL of 10 mM PBS for fluorescence intensity measurement. The fluorescence intensity of Alexa647 modification on complementary DNA was measured with the 635-20 / 680-20 optical module on the PHERAstar FSX. For each measurement, a 10x10 matrix with a hole diameter of 3-5 mm was scanned with the top optics, flashing 10 times at each scan point. The focus height was adjusted for each sample and the increase was set to 2000.
[0119] In order to correctly detect DNA that hybridizes only to covalently immobilized DNA, a wash step is required to remove non-specifically bound DNA. A wash step is included to remove non-covalently bound ssDNA from the microplate wells (step 4, Figure 2 a) non-hybridized ssDNA (steps 7-11, Figure 2 a). It was found that the wrong sequence was not fixed for ssDNA (step 2) or added hybrid DNA (step 6, Figure 2c), washing effectively reduced the fluorescence signal of the negative control back to the baseline level (t-test, p<0.0001). For example, a 50% reduction from step 7 to step 11 is equivalent to removing approximately 8.4x10 10 In preliminary measurements, the density of hybridized DNA was found to be higher in the center of the microplate wells than at the edges ( Figure 2 b). Due to shielding and the reduction in the ratio of sheath area to wall area, the fluid mixing efficiency at the edge of the hole is lower and experiences a lower injected ion flux, which can limit the DNA density near the edge. Therefore, the hybridization density measurements were averaged over a 3 mm diameter circle at the center of the hole (whose overall diameter is 5 mm).
[0120] DNA hybridization characterization was performed for all formulations of PIII (PIII-400, PIII-800) and PAC (no, low, medium, and high nitrogen). Greater fluorescence signals (<3.1x10 10 Molecules / cm 2 ), which shows a higher DNA hybridization density and is also higher on PAC-treated microplates than on PIII-treated microplates (PIII 1.3x10 11 Molecules / cm 2 ,PAC 3.4x10 11 Molecules / cm 2 , one-way ANOVA, p<0.0001)( Figure 2 c, Table 2). Compared with PIII, the DNA hybridization density on PAC was about 2-5 times (1.1-1.6x10 11 Molecules / cm 2 , one-way ANOVA, p<0.0001, and the no nitrogen and low nitrogen PAC formulations had the greatest amount of hybridized DNA overall (4.7-4.8x10 11 Molecules / cm 2 , one-way ANOVA, p<0.0001). There were no significant differences among the four different PIII surfaces, indicating that aluminum foil and treatment time did not affect DNA fixation. The effect of pH on DNA fixation was tested by incubating fixed ssDNA at pH 3 to 8 (step 2, Figure 2 a). For almost all PIII and PAC treated microplates, the highest hybridization density was observed for pH 3 and 4 ( Figure 3 a, b). The DNA fixation capacity of the PIII-treated microplate decreased one month after PIII treatment, but did not decrease further until three months ( Figure 3 c). All PAC samples maintained the same DNA fixation capacity for up to 3 months ( Figure 3d). DNA fixation and hybridization on the no-nitrogen and low-nitrogen PAC samples were further optimized by using freshly prepared hybridization solution and measuring fluorescence intensity from a 3 mm diameter instead of a 5 mm diameter. After further optimization, the average hybridization density on the no-nitrogen and low-nitrogen PAC samples increased to 5.2 x 10 12 Molecules / cm 2 ( Figure 4 ).
[0121] Interestingly, it was found that the measured relative radical density did not correlate with the amount of DNA hybridized to the surface. The relative radical density of the PIII microplate was 5-15 times that of the PAC, but the DNA hybridization capacity was 2-5 times lower. This suggests that the small amount of free radicals on the PAC surface is sufficient for dense DNA immobilization.
[0122] Table 2: Densities of hybridized DNA and immobilized streptavidin for TC, PIII, and PAC microplates
[0123]
[0124] The PAC surface had a higher DNA density than PIII, which could be explained by the higher nitrogen composition that can be protonated on the PAC surface leading to more favorable electrostatic interactions. The highest DNA density was found on the PAC surface with a lower surface nitrogen composition.
[0125] The hydrophilicity of the surface is another important factor that may affect the intermolecular interaction with DNA. Both hydrophilic and hydrophobic surfaces can attract DNA. Hydrophobic surfaces can attract nearby DNA by short-range van der Waals (vdW) forces, while hydrophilic surfaces can attract longer-range DNA by dipole-dipole and hydrogen bonds. However, hydrophilic surfaces are more prone to forming a dense hydration layer, which competes with the intermolecular attraction between the surface and DNA by hydrogen bonds. Therefore, the DNA density on the surface of nitrogen-free and low nitrogen PAC is higher than that of other samples. Explain below: Compared with medium and high nitrogen PAC and all PIII conditions, their relative hydrophobicity minimizes the formation of a hydration layer and maximizes van der Waals forces.
[0126] Example 7 - Immobilization of Streptavidin on PIII and PAC Modified Microplates
[0127] Streptavidin immobilized on plasma treated surfaces is detected directly by fluorescence of covalently modified Cy3 streptavidin. For PAC surfaces, it is also detected indirectly by binding to double biotinylated Alexa647 modified DNA strands. The former quantifies immobilized proteins, while the latter will only detect active proteins on the surface.
[0128] PIII-treated, PAC-treated and untreated microplates were incubated with 40 μL of 10 μg / mL streptavidin-Cy3 (Sigma-Aldrich, P6402) in 10 mM citric acid / sodium citrate buffer at pH 3, 4, 5 or 6 or disodium hydrogen phosphate / sodium dihydrogen phosphate buffer at pH 7 or 8 at room temperature on a shaker for 1 hour. The streptavidin solution was replaced with 200 μL of 1% BSA (in 10 mM PBS, pH 7.4) for 1 hour at room temperature on a shaker to block the remaining active surface. The BSA solution was removed and the wells were rinsed three times with 200 μL of 10 mM PBS. After rinsing, each well was washed three times with 200 μL of 10% Triton in 10 mM PBS. Next, the wells were further rinsed three times with 200 μL of 10 mM PBS, and then the wells were incubated on a shaker at room temperature for 1 hour with 2 μM 5'biotin-modified ssDNA (IDT DNA, Table 3) in 10 mM PBS at pH 7.4. After biotin-DNA incubation, the wells were incubated with complementary DNA modified with Alexa647 as described in the DNA fixation method. The hybridized surface was washed three times with 200 μL of wash buffer 4 (2xSSC+0.05% Tween 20) and then rinsed with 10 mM PBS. PHERAstar FSX fluorescent plate readers with optical modules 540 / 580 and 635-20 / 680-20 were used to detect fixed streptavidin-Cy3 and hybridized complementary Alexa647-DNA, respectively. For each measurement, a 10x10 matrix with a hole diameter of 3-5 mm was scanned with the top optical device, flashing 10 times at each scan point. The focal height was adjusted for each sample and the increase was set to 1000.
[0129] Table 3: Sequences of immobilized DNA, hybridized DNA, and biotinylated DNA to bind to immobilized streptavidin
[0130]
[0131] Similar to DNA, it was also found that streptavidin binding was higher on PAC-treated microplates than on PIII-treated microplates ( Figure 5 a), and all plasma treatment conditions were significantly higher than the untreated control group (0.01x10 11 Molecules / cm 2 , PIII 0.7x10 11 Molecules / cm 2 ,PAC4.9x10 11 Molecules / cm 2 , one-way ANOVA, p<0.0001). In contrast to DNA, the amount of streptavidin bound by PAC in low nitrogen was the highest (2.2x1011 Molecules / cm 2 、Low nitrogen 9.0x10 11 Molecules / cm 2 , Medium Nitrogen 4.3x10 11 Molecules / cm 2 , High Nitrogen 4.0x10 11 Molecules / cm 2 )), while for DNA, low nitrogen and no nitrogen PACs were similarly high. This PAC trend was reproduced for biotin-DNA binding, indicating that the immobilized protein remains active ( Figure 5 b, no nitrogen x10 11 , low nitrogen 12.2x10 11 , Medium Nitrogen 7.3x10 11 , High Nitrogen 7.8x10 11 , biotin-DNA molecules / cm 2 ). By calculation, an average of 2.14 hybridized DNA-biotin molecules bound to each immobilized streptavidin on the surface. The best PIII surface for streptavidin immobilization was PIII-400 with aluminum, but it had about 10 times less streptavidin compared to the optimal PAC conditions. The fixation pH affected the amount of streptavidin immobilized on both PIII and PAC microplates. For the PIII microplate, optimal immobilization was achieved at pH 5 ( Figure 5 c). For PAC microplates, optimal streptavidin immobilization was achieved at pH 5 for PAC without nitrogen and at pH 4-7 for other PAC formulations ( Figure 5 d). For all PIII samples, streptavidin immobilization deteriorated significantly after one month ( Figure 5 e). However, for PAC samples up to 3 months of age, the amount of immobilized streptavidin did not change significantly ( Figure 5 f).
[0132] Example 8 - Comparison of PIII and PAC modified microplates
[0133] The PAC surface was found to have more nitrogen and lower radical density, and was more hydrophobic and more stable than the PIII surface over 3 months. Optimal conditions were obtained for high-density DNA (PAC, 0% or 21% nitrogen, pH 3-4) and streptavidin (PAC, 21% nitrogen, pH 5-7) binding. PAC-activated microplates allow high-density covalent immobilization of functional DNA and proteins in one step without the need for specific attachment chemistries.
[0134] Example 9 - Preventing Accumulation of Plasma Generated Nanoparticles
[0135] The plasma generated nanoparticles were observed to accumulate in the PAC coated 24-well plate. To prevent the plasma generated nanoparticles from falling into the wells, the configuration of the sample holder was modified. Figure 6 The plasma treatment was performed under the three conditions shown.
[0136] Polymer mesh: Square meshes with 3 sizes (3, 4 and 5 mm spacing) were modified from the lid of a tissue culture plate using laser cutting and assembled on the well plate during plasma treatment.
[0137] Conductive Mesh: Stainless steel mesh with 3 sizes, 4 mesh (i.e., 4 openings per linear inch), 10 mesh (i.e., 10 openings per linear inch), and 50 mesh (i.e., 50 openings per linear inch) was cut to cover the plate. The mesh was woven from stainless steel wires to form square gaps with spacing sizes varying from 6 mm to 0.45 mm. Polymer fittings cut out of the lid of the tissue culture plate were used to secure the mesh to the top of the plate. The stainless steel mesh had no conductive connection to the sample holder.
[0138] Faraday cage with mesh cover: The Faraday cage with mesh cover consists of 3 parts: an open container, a mesh cover and a cap for securing the mesh cover to the open container. The open container is made of a conductive metal (e.g., steel, brass, aluminum, etc.) and is sized to accommodate the plate or dish to be coated. The cover is also made of a conductive metal, conforms to the shape of the open container, and is used to electrically connect the stainless steel mesh cover to the open container (i.e., the mesh cover is sandwiched between the cover and the open container). This forms a Faraday cage around the plate or dish. Using the same sample holder and other parameters, the plasma treatment effects of three sizes of mesh (4 mesh, 10 mesh, and 50 mesh) were studied. Figure 7 The construction and dimensions of a Faraday cage suitable for a drilled plate are shown in FIG.
[0139] Plasma treatment was performed using a custom three-chamber system ( Figure 8 ). Place the culture plate (Corning Costar, 24 tissue culture plate) on a sample holder, or on a metal plate, or in a Faraday cage with a mesh cover. Evacuate the system until 5x10 -5The plasma treatment consisted of two steps: surface activation with argon plasma and plasma deposition. Both steps utilized plasma generated by an RF power supply, with the surface activation set to 75 W and the deposition set to 50 W. A pulsed negative bias of 500 V at 3 kHz was applied to the sample holder for a duration of 20 μs. During the surface activation step, the pressure of argon was adjusted in the range of 70-80 mTorr. For the deposition step, a gas mixture containing acetylene, nitrogen and argon was maintained at 110 mTorr with flow rates of 1, 3 and 10 sccm, respectively. The durations for surface activation were 2, 5 and 10 minutes, while the deposition step had a fixed duration of 10 minutes.
[0140] The measurement of PAC thickness and the quantification of nanoparticles were carried out with a silicon wafer and a glass cover slip placed in the hole. PAC thickness was determined using spectral ellipsometry (JA Woollam M2000), while the number of nanoparticles was counted using an Olympus BMX-10 optical microscope. Since the nanoscale size of plasma particles and contamination dust makes them difficult to identify with an optical microscope, we used flow cytometry and scanning electron microscopy (SEM) for further verification. SEM images were captured on silicon wafers using a ZeissSigma HD SEM at magnifications of 1000x and 5000x. In order to reduce surface charging and enable imaging, the sample was coated with a conductive gold layer with a thickness of 5nm. During SEM imaging, an in-lens detector with a working distance of 3-5mm was used. The field emission gun was set at 5kV to facilitate the imaging process.
[0141] When a mesh was used during plasma treatment, the number of nanoparticles decreased. The use of a polymer mesh slightly reduced the particles. The conductive mesh blocked particles more effectively than the polymer mesh, especially when the mesh spacing size became smaller. The Faraday cage with a 50 mesh cover showed comparable particle counts to the untreated control plate (Table 1).
[0142] Table 4: Number of particles counted on each image on coverslips located on different wells under each plasma treatment condition. The results are the average of 3 images taken on each glass coverslip.
[0143]
[0144]
[0145] Flow cytometer Cytek Aurora (USA) was used to count the number of particles in the solution. Plasma treated 24-well plates, plasma treated with mesh and without mesh were supplemented with 200 ml of milliQ water to remove nanoparticles using 4 methods with increasing shear force levels as described below.
[0146] Still: Gently add water to remove particles
[0147] Pipette: Use a pipette to draw up and release water multiple times to remove particles
[0148] Rocker: Add water to the sample and place on a rocker for 5 minutes to remove particles
[0149] Sonication: Apply high power sonication for 5 minutes to remove particles.
[0150] The solution with nanoparticles was then collected and analyzed using flow cytometry (Cytek Aurora, USA).For each sample, a stop volume of 15 μl was set, and the number of nanoparticles detected was recorded by FlowJo.
[0151] Fig. 9 The number of nanoparticles detected in 15 μL of liquid using flow cytometry was compared, and the results showed that the particle count dropped significantly when plasma treatment was performed using a Faraday cage with a 50-mesh cover compared to conventional treatment without a mesh. The high density of nanoparticles in the liquid sample removed from the plate treated without a mesh suggests that these nanoparticles are loosely bound to the PAC and can be easily removed using low shear forces, such as the static method.
[0152] From the SEM images ( Fig.10 ) The nanoparticles formed on the coating were observed. They were present as single particles or particle agglomerates on the coating obtained by plasma treatment without a mesh. In contrast, when a Faraday cage with a 50 mesh cover was used, very few nanoparticles could be found on the transparent and smooth coating.
[0153] The coating thickness was determined by placing a silicon wafer inside the well and measuring the PAC deposited on the silicon surface using spectroscopic ellipsometry. Fig.11 The thickness of the PAC was compared when the silicon wafer was positioned at various locations on the plate. The coating thickness was generally thicker with the stainless steel mesh than with the polymer mesh, especially as the mesh size decreased. Assuming that the polymer mesh cannot conduct away the charge that falls on it, the positive charge will accumulate over time, which reduces the electric field created by the negative bias and therefore also reduces the force that attracts ions from the plasma to create the coating. This is less of a problem with the stainless steel mesh because the charge will be conducted away.
[0154] Fig.12 A comprehensive comparison of PAC thickness between treatment without a mesh and treatment with a Faraday cage with a 50 mesh cover is provided. When no mesh was used, the PAC thickness was measured to be 1.13 ± 0.35 nm. However, when the mesh was used, the PAC thickness increased to 1.89 ± 0.54 nm.
[0155] Example 10 - Comparison of Cell Culture in Plasma Treated Wells
[0156] The effect of plasma treatment on the differentiation of induced pluripotent stem cells (iPSCs) into cardiomyocytes (CMs) was examined on untreated (UT), plasma-treated without mesh (-Mesh), and plasma-treated with a Faraday cage with a 50-mesh lid (+Mesh) 24-well plates, followed by coating with laminin 521 (LN521).
[0157] Briefly, laminin-521 (LN521) was added to PBS (containing Ca 2+ and Mg 2+ ) was diluted to a concentration of 10 μg / mL and 200 μL was added to each well of the UT, -Mesh and +Mesh treated wells. After incubation at 4°C overnight, the wells were washed. Human induced pluripotent stem cells (iPSCs) (Gibco Episomal iPSCLine; A18945) were cultured on Matrigel in 6-well plates (Corning Costar) in mTeSR Plus basal medium supplemented with Plus 5X supplement (STEMCELL, #100-0276), passaged and cultured at approximately 3x10 5 Cells / well were seeded into the wells at a density of 1:1. The next day after seeding (day -1), fresh mTeSR Plus basal medium with Plus5X supplement was added to dilute out the ROCK inhibitor. The next day (day 0), CM differentiation medium A (STEMCELL, #05010) was added for two days. Differentiation medium B (STEMCELL, #05010) was added on day 2, followed by differentiation medium C (STEMCELL, #05010) on days 4 and 6. Finally, differentiation medium was replaced with cardiomyocyte maintenance basal medium (STEMCELL, #05010) on day 8, and continuously supplemented every 2 days.
[0158] The progress of iPSC conversion to beating cardiomyocytes (CM) was measured using a Nikon microscope with a 4x objective. The amount of beating colonies as a percentage of the visible area in the eyepiece was recorded at 9 different locations and averaged to approximate the relative percentage of the total wells containing beating colonies. Each sample was repeated three times, giving n = 3 data points, plotted on GraphPad (GraphPad Software, Version 9.5.1, San Diego, California).
[0159] Fig.13+Mesh was shown to provide a stable surface on which iPSCs could grow and differentiate into CMs. +Mesh outperformed -Mesh, which in turn outperformed UT. It was hypothesized that this was due to the increased number of nanoparticles in the wells treated with UT and -Mesh, to which laminin binds and is washed away during medium exchange, exposing areas without laminin coating. In contrast, the wells of +Mesh had a uniform PAC coating covalently bound to laminin and fewer nanoparticles.
Claims
1. A method for coating a plastic surface, the method comprising: (a) treating the plastic surface with ions under a pulse bias; as well as (b) depositing plasma on the plastic surface by plasma enhanced chemical vapor deposition (PECVD) of a gas mixture comprising acetylene and argon under a pulsed bias, wherein a mesh is placed over the plastic surface such that the plasma passes through the mesh before being deposited on the plastic surface, and wherein the method produces a plasma activated coating (PAC) covalently bound to biomolecules on the plastic surface.
2. The method of claim 1, wherein the ions are argon ions.
3. The method according to claim 1 or 2, wherein the gas mixture further comprises nitrogen.
4. The method according to any one of claims 1 to 3, wherein the atmospheric percentage of nitrogen in the gas mixture is about 35% or less.
5. The method according to any one of claims 1 to 4, wherein the atmospheric percentage of nitrogen in the gas mixture is about 21%.
6. The method according to any one of claims 1 to 5, wherein the treatment with ions is performed at an RF power of about 75 W and a negative pulse bias of about 500 V for about 2 minutes.
7. The method of any one of claims 1 to 6, wherein the plasma deposition is performed at a plasma discharge of about 50 W and a negative pulse bias of about 500 V for about 10 to about 30 minutes.
8. The method according to any one of claims 1 to 7, wherein the negative pulse bias is applied at a frequency of about 3 kHz and a pulse duration of about 20 μs.
9. The method of any one of claims 1 to 8, wherein the mesh is formed from a conductive metal.
10. The method of claim 9, wherein the mesh forms a lid of a Faraday cage surrounding the plastic surface.
11. A method according to claim 9 or claim 10, wherein the conductive metal is stainless steel.
12. The method according to any one of claims 1 to 11, wherein the plastic surface has a non-planar geometry.
13. The method according to any one of claims 1 to 12, wherein the plastic surface is a microplate well or a culture dish.
14. The method according to any one of claims 1 to 13, wherein the plastic is polystyrene.
15. The method of any one of claims 1-14, wherein the biomolecule is a nucleic acid or a protein.
16. The method according to any one of claims 1 to 15, wherein the PAC has any one or more properties selected from the group consisting of: a surface nitrogen concentration of about 4 to about 14%; A free radical relative density of about 0.016 to about 0.021; an average absorption of about 0.052 to about 0.056 au at 450 nm; A thickness of about 1 nm to about 10 nm; About 2x10 11 About 5x10 11 Molecules / cm 2 hybridize DNA at a concentration of; and About 2x10 11 About 9x10 11 Molecules / cm 2 The concentration of streptavidin was fixed.
17. A plastic surface coated with a plasma activated coating (PAC), wherein the PAC covalently binds biomolecules and has properties selected from any one or more of the following: a surface nitrogen concentration of about 4 to about 14%; A free radical relative density of about 0.016 to about 0.021; an average absorption of about 0.052 to about 0.056 au at 450 nm; A thickness of about 1 nm to about 10 nm; About 2x10 11 About 5x10 11 Molecules / cm 2 hybridize DNA at a concentration of; and About 2x10 11 About 9x10 11 Molecules / cm 2 The concentration of streptavidin was fixed.